Análisis histórico tendencial del proceso de formación del componente investigativo en la carrera de Medicina - Marjories Mirabal Nápoles; Bárbara María Carvajal Hernández; Mayelín Soler Herrera; Alberto Bujardón Mendoza (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
Introduction: given the growing complexity of the health problems of the population, it is essential to improve the research component in future doctors to take on this challenge and act in correspondence with the context. Objective: to refer to the trends that has characterized the training process of the research component in the Medicine career. Methods: a qualitative research with a historical approach was carried out, based on the documentary review, the chronological sub-method and the use of key informants, as predominant methods to develop the objective of this study. Results: the theoretical systematization carried out made it possible to determine the historical-pedagogical milestones to describe the assumed indicators, their progress in each of the stages and elucidate the trends that have characterized said process. Discussion: the formation process of the investigative component in the Medicine career has been on the rise with the improvement of the study plans and programs. However, insufficiencies still persist, given, among other factors, by the unsuccessful projection from the basic biomedical sciences, to communicate the results of the student's research activity, with the use of available technologies in correspondence with the context.